2022
DOI: 10.1007/s13644-022-00523-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Religiosity and Reliance on God during the COVID-19 Pandemic: A Protective Role under Conditions of Financial Strain?

Abstract: Background The COVID-19 pandemic was one of the most devastating disasters of the twenty-first century and has exacted a steep health and economic toll. During times of suffering caused by the pandemic, religion/spirituality may prove to be a consistent and valuable coping resource. Purpose We situate changes in religious importance and reliance on God as key aspects of religious life that may be important coping mechanisms in response to pandemic-related financial hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 94 publications
1
7
0
Order By: Relevance
“…Our study also demonstrated that meaning-focused coping positively correlated with behaviors that promote well-being. This result is in line with those of previous studies, in which meaning-focused coping was positively associated with positive affect (including pain control) over time in somatic patients [ 55 ], and meaningful attitudes to transcendence were associated with a lower level of psychological distress during the COVID-19 pandemic [ 78 ]. Similarly, Ziółkowska et al [ 79 ] showed that meaning-focused coping (measured as positive reappraisal) was a predictor of positive emotions in children diagnosed with cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Our study also demonstrated that meaning-focused coping positively correlated with behaviors that promote well-being. This result is in line with those of previous studies, in which meaning-focused coping was positively associated with positive affect (including pain control) over time in somatic patients [ 55 ], and meaningful attitudes to transcendence were associated with a lower level of psychological distress during the COVID-19 pandemic [ 78 ]. Similarly, Ziółkowska et al [ 79 ] showed that meaning-focused coping (measured as positive reappraisal) was a predictor of positive emotions in children diagnosed with cancer.…”
Section: Discussionsupporting
confidence: 92%
“…These differences may help to explain divergent patterns of health and well-being during the COVID-19 pandemic. Perhaps relatedly, scholars of religion and health have long argued that divine beliefs play an important role in the stress process, shaping individuals’ access to coping resources and their appraisal of stressful circumstances as threatening or manageable (Louie et al 2022; Schieman and Bierman 2011; Upenieks and Ellison 2022). An analogous, broader process might occur in the political arena, as novel social threats are interpreted through a political lens.…”
Section: Discussionmentioning
confidence: 99%
“…It includes a fundamental belief in God and is measured by prayer, church attendance, and meditation frequency. For example, some scholars have found that research focused on the role of stress within a stress process model has shown that individual religiosity buffers the adverse association between financial strain and mental health ( Upenieks and Ellison 2023 ). Recent trends suggest declines in Black youth religiosity, especially during the last two years of high school when many become disinterested in formal religious involvement and stop attending religious services regularly.…”
Section: Introductionmentioning
confidence: 99%